Nail lesions as a main manifestation of lichen nitidus - Sobjanek, Michał; Lakomy, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction . Lichen nitidus (LN) is a rare, chronic, inflammatory dermatosis usually affecting children and young adults. Nails involvement is very rare. Until now, 7 cases of LN with nail involvement have been described. Objective. To present a rare case of childhood lichen nitidus where trachyonychia was the main manifestation of the disease. Case report. A 7-year-old, Caucasian, previously healthy boy presented thumbnail longitudinal ridges, distal splitting and subungual hyperkeratosis for 7 months. Numerous mycological and bacteriological examinations were negative. Dermatological examination also revealed erythematous lesions on the proximal nail fold as well as small skin-pigmented papules on the thumb. Similar papules grouped into patches were also observed on the upper limbs, trunk and forehead. Treatment was not recommended. Conclusions . Lichen nitidus may rarely affect nails and should be considered as a possible cause of nail lesions in childhood.